Dynamic postural stability in individuals with ACL reconstruction versus healthy controls with insights into sex differences: A cross-sectional study - Wasim Labban; Juan Forero; Lindsey Westover; Mark Sommerfeldt; Stephanie Nathanail; Lauren Beaupre (PLoS ONE, 2026)
Objectives To compare dynamic postural stability, measured by time to stabilization (TTS) and postural stability indices (PSI), after double-leg counter-movement jump (CMJ) landing in individuals 9–24 months following anterior cruciate ligament reconstruction (ACLR) and healthy controls. Additionally, to explore the effect of sex and ACLR status on postural stability. Methods This cross-sectional laboratory-based study included 41 participants: 21 individuals (10 females) 9–24 months post-ACLR and 20 healthy controls (10 females). Participants performed double-leg countermovement jumps (CMJs) on force plates, landed, and maintained the landing position for 10 seconds. Time to stabilization (TTS), defined as the time (s) required for the ground reaction force to reach and maintain a stable state following landing, and postural stability index (PSI), a composite measure of the ability to maintain equilibrium during the transition from dynamic to static conditions, were calculated and compared between groups. Results The ACLR group exhibited significantly higher TTS values than healthy controls, indicating a longer duration to achieve stability. Specifically, the resultant vector TTS when combined from both force plates (RVTTS-C), and the vertical TTS in the operated leg (VTTS-op) was higher in the ACLR than the healthy controls (p = 0.03, p = 0.02, respectively). Furthermore, males with ACLR demonstrated higher VTTS combined (VTTS-C) and VTTS-op than females post-ACLR (p = 0.03, p < 0.01, respectively) and higher VTTS-op compared to healthy males (p = 0.03). There were no differences in PSIs between groups. Conclusion Our study revealed significant deficits in dynamic postural stability in individuals post ACLR, with notable sex differences. The findings suggest a need for targeted neuromuscular rehabilitation to improve landing stability post ACLR and reduce the risk of secondary injury. Further research is needed to understand sex-specific postural stability mechanisms for tailored rehabilitation.